The Usage of QR Codes among Young Generation in Johor - Tay Siew Qi,; Fernandez, Dahlia (Research in Management of Technology and Business, 2021)
QR code is define as an identification mark for a type of matrix barcode. Based on the previous research, there is still lack of research conducting the IS Success Model by doing the qualitative method in Malaysia. The purpose of the study is to discuss the usage of QR code among the young generation in Johor. This research used the qualitative method with semi-structured interviews for the data collection. In this study, the researcher focused on the young generation in Johor among the range of age from 18 to 30 years old for the interview sessions. Around 15 respondents from a population of 3.76 million peoples were selected to take part in the interviews. The type of interviews used in this study is semi-structured. The reason of using QR codes were  experience new things, social media, making online payment, request new friends, save information, questionnaire and attendance of classes. QR codes were beneficial to others by provided detail information easily, connect the online and offline media, cashless payment, and record attendance. The challenges were speed of internet connection, apps installation, inconvenient for elderly people, management of shops, security risks and cybercrime. QR codes can be innovated in future that widely used in the medical field, new marketing resources and improved ability of connection. They can use QR codes to punch cards instead of fingerprints that reduced system error.